Mobilizing Sustainable Investment for Vietnam’s Coastal Dike System: Determinants and Policy Solutions - Bui Thi Ngoc Lan; Dao Truong Thanh; Le Cong Thanh; Trinh Thi Phin (International Journal of Sustainable Construction Engineering and Technology, 2026)
Coastal infrastructure development, particularly through sustainable investment in dike systems, represents a critical measure for enhancing climate adaptation and protection in vulnerable regions. In Vietnam, which faces escalating threats from climate change and sea-level rise along its extensive coastline, the need to upgrade and maintain coastal dikes is urgent. However, significant deterioration of existing dikes, coupled with constrained state budget resources, presents major challenges to financing such infrastructure. This study aims to identify the determinants of investment demand for Vietnam’s coastal dike system and to propose policy solutions for mobilizing sustainable financing. The research employs a mixed-methods approach, combining exploratory quantitative analysis of data from 21 coastal provinces with qualitative SWOT assessment and international policy benchmarking. Findings reveal that the length of substandard dikes is the primary factor correlated with investment demand, while socio-economic indicators and typhoon frequency show weaker associations. Based on these results, the study develops an integrated six-pillar financing framework, emphasizing scientific capital allocation, a diversified financial ecosystem, transparent governance, innovative instruments, strategic international cooperation, and robust monitoring. The framework draws on lessons from countries such as Japan and the Netherlands, and proposes mechanisms including a dedicated coastal dike infrastructure fund, public-private partnerships, green financial instruments, and enhanced international cooperation. The study concludes that mobilizing diversified and timely resources is essential not only to address a projected adaptation financing gap of USD 6–12 billion for 2025–2030, but also to build long-term resilience, protect coastal communities, and support sustainable development in Vietnam.